SOCIAL CLASS IN VICTORIA AVEYARD’S RED QUEEN - Trisni Dian Ningsih; Yoseph Bavo Agung Prasaja (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This study is about an analysis of social class in Victoria Aveyard’s Red Queen. This thesis aims to analyse social class in the novel. Qualitative research is used in this study. The problem statements are about social class and the relationships that exist between them. In the research, the analysis is conducted by using Marxist theory. The writer also finds that there are kinds of social class and their relathionships. The Silvers are classified as the borguisie, while the Reds are classified as the proletariat. The bourgeoisie in this novel is known as the royals, the nobility, and the rich people who are filled by the Silvers, while the proletariat is the Reds. They live to serve the Silvers, they work as servants, apprentices, and avant-garde soldiers. As Marx said that between these two classes there will be various kinds of conflicts. These conflicts arise because of inequalities or differences between them. Differences in social class can be seen in how social groups get their social status, use their privileges, and take advantage of their prestige. There is oppression of the Reds people, making them want to be free from the upper class oppression or exploitation through struggle against the Silvers. As for the efforts made by the Reds to avenge the inequality and oppression of the Silvers, it was through rebellion. The uprisings are portrayed epicly in this novel.